2015
DOI: 10.1515/aiht-2015-66-2589
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity evaluation of different pulp capping materials: a comparative study

Abstract: Direct pulp capping covers the exposed surface of the pulp to maintain its vitality and preserve its functional and biologic activity. The aim of the present study was to compare the biocompatibility effects of seven different pulp-capping materials in vitro: Dycal®, Calcicur®, Calcimol LC®, TheraCal LC®, ProRoot MTA®, MTA-Angelus®, and Biodentine®. Using the Transwell insert methodology by Alamar blue test, we evaluated the cytocompatibility of the above mentioned materials towards murine odontoblasts cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
5
30
0
1
Order By: Relevance
“…In our study, change in the medium pH owing to the setting phase of the capping agents may partially contribute to the observed inhibitory effects. Consistent with previous studies, Dycal has an overall negative effect on HDP cells in this study, exhibiting cytotoxic effects and impeding growth and differentiation of pulp cells (8,29,31).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, change in the medium pH owing to the setting phase of the capping agents may partially contribute to the observed inhibitory effects. Consistent with previous studies, Dycal has an overall negative effect on HDP cells in this study, exhibiting cytotoxic effects and impeding growth and differentiation of pulp cells (8,29,31).…”
Section: Discussionsupporting
confidence: 92%
“…Although calcium hydroxide has been widely accepted in clinical practice, studies have shown it may be cytotoxic due to high alkalinity. It was reported that Calcicur (21% cell vitality in 3-day MTT test) was more cytotoxic than MTA or the negative control (26-35% cell vitality in the same test) 8) . Another study using rat subcutaneous tissue showed that calcium hydroxide, such as UltraCal XS, caused an intense inflammatory reaction and a coagulative necrosis at 7 days, but the inflammatory process was significantly reduced at 30 days 9) .…”
Section: Calcium Hydroxide and Resin-modified Calcium Hydroxidementioning
confidence: 97%
“…The hydrophilic matrix allows higher calcium and hydroxide release, which are very important in protecting pulp their ability to stimulate dentin formation and provide antibacterial action (high alkalinity), respectively 6,31,33) . Both TheraCal LC and resin-modified calcium hydroxide were shown to be more cytotoxic to murine odontoblasts cells and human dental pulp stem cells than resin-free calcium silicates, such as Biodentine, MTA Angelus, and ProRoot MTA, but they showed similar or lower cytotoxicity than Dycal (vitality with MTT test after 72 h: resin-modified materials: 14-15%, resin-free MTA 28-35%, Dycal 9%; number of vital cells with Alamar blue tests after 72 h: resin-modified materials: 33000-35000, resin-free MTA 333000-533000, Dycal 30000) 8,34) . However, this cytotoxicity might be due to the uncured monomers in the oxygen inhibition layer on the surface of TheraCal LC test samples during sample preparation in the laboratory (exposure to air/oxygen).…”
Section: Calcium Silicates and Resin-modified Calcium Silicatesmentioning
confidence: 98%
See 2 more Smart Citations